Protection of national identity in the European Convention on Human Rights. Notes on !e background of the decision Aksu v. Turkey = Ochrona tożsamości narodowej w Europejskiej Konwencji o Ochronie Praw Człowieka Uwagi na tle orzeczenia Aksu przeciwko Turcji - Markiewicz-Stanny, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a discussion of ethnic identity or national point of view of human rights in the region. Provisions of the European Convention on Human Rights and Fundamental Freedoms expressly relating to nationality come down to the prohibition of discrimina-tion. However, the European Court of Human Rights seems more and more decisions in which the issue of ethnicity is in conjunction with violations of Convention rights. Aksu v. Turkey case is the exemplification of such a situation.
Keywords: ETC; Romowie; Turcja; mniejszości narodowe; Roms; Turkey; national minority